Status of Fruit Farming in Central Valley of Khyber Pakhtunkhwa - Shah, Nisar Ali; Farooq , Arshad; Hassan, Abdul; Khan , Abdul Samad; Niazi, Muhammad Azam; Farooq, Umar (Asian Journal of Agriculture and Rural Development, 2014)
This retrospective study was conducted in four districts of Khyber Pakhtunkhwa namely Charsadda, Nowshera, Mardan and Peshawar during January February, 2013 to examine the status and factors affecting fruit orchards. A total of Sixty four fruit orchards growers were interviewed on the basis of land acquisition. Data indicates that farmer areas for citrus and planted Stone fruit such as peach, plum and apricot were declined in the last 10 years while the area under pear and loquat were increased. The study results also indicate that a number of factors were affecting fruit orchards. These problems were ranked as (1) diseases/insects, followed by (2) high price, (3) water shortage problem, (4) adulteration in inputs, (5) marketing problem and (6) non-availability of credit. It is concluded that various factors are responsible for the decline in production of fruit orchards. It is thus, recommended that agriculture department should regularly disseminate technical-know-how regarding improved fruit orchards management practices through training, field days and workshop and other awareness programmes for fruit orchards growers. The government should also keep check and balance on price and quality of inputs to encourage fruit orchard growers to increase their production.